Pemanfaatan Customer Internal Meaning Dalam Proses Komunikasi Pemasaran Pada Padmaning Garden - Bidhari, Kinanti Padma; Teguh, Monika (Jurnal Spektrum Komunikasi, 2025)
As one of the largest ornamental plant-producing countries, Indonesia benefits from its fertile soil and tropical climate, making the cultivation of ornamental plants relatively easy. The agriculture industry in Indonesia, particularly the ornamental plant and nursery sector, has seen significant growth. One of the key players in this sector is Padmaning Garden, which has been operating since 2020 and handles both export and import sales. Over the course of four years, Padmaning Garden has successfully established and maintained its nursery business by implementing effective marketing communication strategies. This study examines the application of "Customer Internal Meaning" in marketing communications at Padmaning Garden, a company offering garden and landscape services. "Customer Internal Meaning" refers to a deep understanding of customers' perceptions, values, and motivations. The research aims to explore how customer perceptions influence the effectiveness of marketing communications and how their engagement can enhance customer satisfaction and loyalty. This study contributes to the marketing communication literature by focusing on the agricultural sector, specifically ornamental plant businesses. It also identifies how understanding customer internal meaning can improve marketing strategies and deepen customer relationships. A qualitative approach is employed in this research, utilizing in-depth interviews with the owner, marketing manager, and customers of Padmaning Garden. Data is further supplemented by content analysis of the company's marketing communication materials, such as social media posts and online marketplace content. This research is expected to offer insights into how customer internal meaning can be utilized to enhance marketing communications in the agricultural industry.